1993
DOI: 10.1093/ije/22.3.548
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Prediction Rule for American Cutaneous Leishmaniasis in Colombia

Abstract: Neither parasitological nor molecular diagnosis of leishmaniasis is widely available in clinical settings where American cutaneous leishmaniasis (ACL) is endemic. Therefore four clinical prediction rules for ACL were developed which incorporated physical examination findings (clinical rule), physical examination and leishmanin skin test (LST) (clinical-LST rule), physical examination and historical information (clinical-historical rule), or physical examination, historical information and LST (clinical-histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
10
0
5
Order By: Relevance
“…A clinical predictive rule for the diagnosis of ATL has already been suggested 37 and validated 38 . Anatomopathological scoring systems for the classification and prognosis of neoplasms are well known and have been used for several decades 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…A clinical predictive rule for the diagnosis of ATL has already been suggested 37 and validated 38 . Anatomopathological scoring systems for the classification and prognosis of neoplasms are well known and have been used for several decades 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…27:1186-1193, 1998). The reference standard for cases of leishmaniasis consisted of combined laboratory criteria (conventional laboratory methods or supplemental laboratory methods) and previously evaluated clinical criteria (40). A case of CL was required to meet either the laboratory or the clinical criteria.…”
Section: Methodsmentioning
confidence: 99%
“…In order to apply the reference standard and thereby identify additional cases of CL, supplemental laboratory procedures were performed and clinical prediction rule criteria established in a prior study (40) were utilized when all conventional methods were negative for the initial clinical sample. The additional specimens were obtained and evaluated by the three assays described above and by inoculation of macerated biopsies into hamsters.…”
Section: Methodsmentioning
confidence: 99%
“…Differential diagnosis is important because diseases of other etiologies (e.g. leprosy, skin cancers, tuberculosis) with a similar clinical spectrum to leishmaniasis are often present in leishmaniasis-endemic areas (Weigle et al, 1993a). Although many researchers have suggested that taxonomic discrimination of Leishmania infecting LCL patients (at least distinguishing L. (Viannia) and L. (Leishmania) subgenera) is important for therapeutic decisions (Rodriguez et al, 1994;Mimori et al, 1998), this is not practiced in any country, not least because there is currently insufficient evidence to tailor treatment protocols according to parasite type.…”
Section: Advances In Diagnosismentioning
confidence: 99%